2020
DOI: 10.3390/genes11091094
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Link between Polyphenols, Aging and Age-Related Diseases

Abstract: Aging is a complex process mainly categorized by a decline in tissue, cells and organ function and an increased risk of mortality. Recent studies have provided evidence that suggests a strong association between epigenetic mechanisms throughout an organism’s lifespan and age-related disease progression. Epigenetics is considered an evolving field and regulates the genetic code at several levels. Among these are DNA changes, which include modifications to DNA methylation state, histone changes, which include mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 146 publications
0
44
0
Order By: Relevance
“…However, no consensus could be established on the effect of GSPE on fat accumulation when administered preventively, which suggests that age may affect the long-term GSPE effect seen previously in young rats [ 31 ]. Dietary polyphenols, such as resveratrol and quercetin, are believed to promote longevity and life expectancy [ 38 ], while scientific evidence suggests they can also modulate epigenetic patterns [ 39 , 40 ]. Our group has also shown that the long-lasting effects of GSPE in young rats are mediated, at least partially, by epigenetic modifications in the intestine [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no consensus could be established on the effect of GSPE on fat accumulation when administered preventively, which suggests that age may affect the long-term GSPE effect seen previously in young rats [ 31 ]. Dietary polyphenols, such as resveratrol and quercetin, are believed to promote longevity and life expectancy [ 38 ], while scientific evidence suggests they can also modulate epigenetic patterns [ 39 , 40 ]. Our group has also shown that the long-lasting effects of GSPE in young rats are mediated, at least partially, by epigenetic modifications in the intestine [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has also shown that the long-lasting effects of GSPE in young rats are mediated, at least partially, by epigenetic modifications in the intestine [ 41 ]. In the present study, the loss of long-lasting GSPE effects in aged animals may be due to the deep, epigenetic modifications that are linked to the ageing process [ 40 ]. Our results therefore suggest that aged animals are more prone to obesity and difficulty in losing weight.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is categorized by a decline in tissue and organ functions with an increased risk of mortality [ 50 ]. In this study, we found that patients with osteoporosis were older and the proportion of women with osteoporosis was significantly higher among the 100 participants, which is consistent with the previous reports [ 43 45 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key enzymes that modulate this process are DNA methyltransferase enzymes (DNMT). They transfer a methyl group to the 5 carbon position of cytosine to form 5-methylcytosine [56].…”
Section: Dna Methylationmentioning
confidence: 99%
“…The process of histone modification occurs because of the translational and posttranslational modifications (PTMs) [56]. These PTMs occur mostly within the histones' N-terminal tail or within their globular domain and include a variety of processes such as acetylation, biotinylation, phosphorylation, ubiquitination, SUMOylation, ADP ribosylation, proline isomerization, citrullination, butyrylation, propionylation, and glycosylation [57].…”
Section: Histone Modificationsmentioning
confidence: 99%